Diseño del plan de contingencias de historias clínicas electrónicas en la Clínica Integral de Fracturas Lomas Verdes S.A.S., Lorica-Córdoba, 2022 (2022)
Introduction: The clinical history is the only valid document to demonstrate the type of care that a user has received, it is a true reflection of the quality of care provided by the health professional. Objective: to design a contingency plan for medical records in the Lomas Verdes Integral Fracture Clinic in the municipality of Lorica. Methodology: application of a checklist based on the health accreditation manual. Results: With the design of the contingency plan, accreditation standards 150 are complied with. Code: (GI9) that contemplates the management of information related to clinical records, whether in physical or electronic media, guarantees quality, safety and their accessibility and standard 151. Code: (GI10) There is a contingency plan designed, implemented and evaluated that guarantees the normal operation of the organization's information systems, whether manual, automated, or both. Any dysfunction in the system is collected, analyzed and resolved. This includes mechanisms to prevent adverse events related to the management of information systems, especially alarms in medical records. Conclusions: compliance with health regulations is essential in the process of continuous improvement by allowing the adoption of strategies that guarantee adequate management of information, custody and preservation of medical records and that contribute to patient safety